2014
DOI: 10.1038/mtna.2014.31
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Target Site in HIV-1 Gag RNA is Accessible to Inhibition by Both an HDV Ribozyme and a Short Hairpin RNA

Abstract: Antisense-based molecules targeting HIV-1 RNA have the potential to be used as part of gene or drug therapy to treat HIV-1 infection. In this study, HIV-1 RNA was screened to identify more conserved and accessible target sites for ribozymes based on the hepatitis delta virus motif. Using a quantitative screen for effects on HIV-1 production, we identified a ribozyme targeting a highly conserved site in the Gag coding sequence with improved inhibitory potential compared to our previously described candidates ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…34,83,84 For virus production, HEK 293T cells were transfected with HIV-1 provirus pNL4-3 and supernatants were harvested 48 h post-transfection. Viral content of supernatant was evaluated by performing a reverse-transcriptase assay as described.…”
Section: Rredi-f-mentioning
confidence: 99%
See 2 more Smart Citations
“…34,83,84 For virus production, HEK 293T cells were transfected with HIV-1 provirus pNL4-3 and supernatants were harvested 48 h post-transfection. Viral content of supernatant was evaluated by performing a reverse-transcriptase assay as described.…”
Section: Rredi-f-mentioning
confidence: 99%
“…Viral content of supernatant was evaluated by performing a reverse-transcriptase assay as described. 84 For the infection, volumes of supernatant corresponding to 1 or 2 million cpms of reverse transcriptase activity were applied to Jurkat cells for 3 h before washing.…”
Section: Rredi-f-mentioning
confidence: 99%
See 1 more Smart Citation
“…We previously screened HIV-1 RNA for conserved ribozyme target sites (35,36) based on the specific on/off adaptor (SOFA) hepatitis delta virus (HDV) ribozyme motif (37)(38)(39). A target site in the Gag coding sequence was identified that was highly conserved and accessible to a ribozyme and an shRNA (36).…”
mentioning
confidence: 99%
“…The third solution involves identifying novel, genetically conserved sequences of HIV which do not usually undergo mutation. Targeting these stable sites would favour the success of RNAi [114]. Finally, RNAi techniques are also being designed to restrict the 'genetically more stable' host factors that help in HIV replication (discussed later under strategies to enhance target cell resilience to HIV infection).…”
Section: Rna Based Therapeuticsmentioning
confidence: 99%